Understanding the adhesion phenomena in carbohydrate-hydrogel-based systems: Water up-take, swelling and elastic detachment. (20th October 2015) - Caccavo, Diego; Lamberti, Gaetano; Cascone, Sara; Barba, Anna Angela; Larsson, Anette
Highlights: Quantitative studies of bio-adhesion by experiments and modeling were carried out. An in-vitro model of bio-adhesion was proposed and validated, in which the detachment forces were monitored by means of a texture analysis. A simple mathematical model was proposed and it was found able to reproduce all the observed behaviors, in term of weight gain and of the system's mechanical response. Abstract: The bio-adhesion is a complex phenomenon which takes place when two materials (at least one of biological nature, the other usually is a polymeric one) are held together for extended periods of time, usually for local drug delivery purposes. Despite bio-adhesion is widely exploited in commercial pharmaceuticals such as the buccal patches, the underlying phenomena of the process are not completely clarified yet. In this study experimental tests, in which the role of biological membranes is played by a water-rich agarose gel whereas patches are mimicked by hydrogel tablets (made of Carbopol or of Carbopol added with NaCl), have been used to analyze the behavior of the model system above described. Tablets have been forced to adhere on the agarose gel, and after a given contact time they have been detached, recording the required forces. Furthermore weight gain of the tablets (the water transported from the agarose gel toward the tablet) has been quantified. Water transport (during the time in which the contact between tablet and agarose gel is held) and elastic part of mechanical response during the detachment are modelled to achieve a better understanding of the adhesion process. Both the two sub-models nicely reproduce, respectively, the weight gain as well as the swelling of the Carbopol tablets, and the point at which the mechanical response ceases to be purely elastic.